2012
DOI: 10.1038/nn.3108
|View full text |Cite
|
Sign up to set email alerts
|

Activation of adult-born neurons facilitates learning and memory

Abstract: Thousand of local interneurons reach the olfactory bulb of adult rodents every day, but the functional effect of this process remains elusive. By selectively expressing channelrhodopsin in postnatal-born mouse neurons, we found that their activation accelerated difficult odor discrimination learning and improved memory. This amelioration was seen when photoactivation occurred simultaneously with odor presentation, but not when odor delivery lagged by 500 ms. In addition, learning was facilitated when light fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
199
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(217 citation statements)
references
References 49 publications
7
199
1
1
Order By: Relevance
“…At the cellular level, cortical excitatory inputs onto GCs exhibit LTP (10,33), a feature that can ultimately facilitate GC spiking and promote feed-forward inhibition onto M/T cells (33). This feedforward inhibition may participate in gain control of odor-evoked responses in M/T cells, as observed when it is mimicked by optogenetic activation of adult-born GCs, specifically in the β-frequency (16). In addition, this top-down feed-forward inhibition could help synchronize distant M/T cells, thereby facilitating the bottom-up flow of information to the OC pyramidal cells by increasing input coincidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the cellular level, cortical excitatory inputs onto GCs exhibit LTP (10,33), a feature that can ultimately facilitate GC spiking and promote feed-forward inhibition onto M/T cells (33). This feedforward inhibition may participate in gain control of odor-evoked responses in M/T cells, as observed when it is mimicked by optogenetic activation of adult-born GCs, specifically in the β-frequency (16). In addition, this top-down feed-forward inhibition could help synchronize distant M/T cells, thereby facilitating the bottom-up flow of information to the OC pyramidal cells by increasing input coincidence.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, olfactory memory is impaired when adult neurogenesis is compromised (13,15). Conversely, the selective stimulation of adult-born neurons improves olfactory learning and memory (16), suggesting that these neurons are part of the olfactory memory engram (17). Although recent transsynaptic strategies have revealed the presynaptic connectivity of adult-born neurons (18,19), little is known about how learning affects their structural and synaptic plasticity or which circuits and presynaptic cells are functionally recruited with them during associative learning.…”
mentioning
confidence: 99%
“…Mechanisms related to altered cell turnover of OSNs may play an important role. Previous work has shown that associative olfactory learning modulates the survival of newborn neurons and increases the survival of adultborn neurons in the OB (29)(30)(31)(32). Although these studies investigated the contribution of olfactory neurogenesis to learning at the level of the OB, learning-dependent regulation of epithelial olfactory neurogenesis, in which OSNs are in direct contact with environmental cues, may play a similarly and perhaps even greater role in shaping sensory epithelial responses to learning.…”
Section: Discussionmentioning
confidence: 99%
“…adult neurogenesis | synaptic tracing | adult neural stem cell | functional integration | pseudotransduction I n most mammals, the dentate gyrus (DG) of the hippocampus and the olfactory bulb (OB) are remodeled throughout life by the incorporation of new neurons, with accruing evidence pointing toward unique roles of these neurons in information processing (1)(2)(3)(4). Crucial for a better understanding of the contribution of adult-generated neurons to circuit function is the identification of their connectome and how it develops during the process of integration.…”
mentioning
confidence: 99%